Isolasi Bakteri Endofit dari Tanaman Bangle (Zingiber cassumunar Roxb.) dan Uji Aktivitas Antibakterinya terhadap Bakteri Penyebab Penyakit Kulit Staphylococcus epidermidis dan Pseudomonas aeruginosa - Wulansari, Anggistina; Aqlinia, Maulida; Wijanarka, W; Raharja, Budi (Berkala Bioteknologi, 2019)
Data fromthe Indonesian Health Profile 2010 showed that skin disease was ranked third of the 10 most common diseases in outpatients in hospitals Indonesia. Staphylococcus epidermidisand Pseudomonas aeruginosaare pathogenic bacteria that can cause skin diseases. The bangle plant (Zingiber cassumunar Roxb.) is one of the traditional medicinal plants that is widely used to treat skin diseases and has side effects that are safer than chemical drugs. Endophytic bacteria can produce the same antibacterial bioactive compounds as their host plants, so there is no need to cut down the original plants to be taken as simplicia. The purpose of this study was to isolate endophytic bacteria from bangle plants and find out their antibacterial activity in inhibiting the growth of bacterial causes of Staphylococcus epidermidis and Pseudomonas aeruginosa. The method used to test antibacterial activity is the diffusion method to use paperdisk. The isolation results obtained 16 bacterial isolates from the rhizomes, roots, stems and leaves. The screening results obtained 3 potential endophytic bacterial isolates namely Da_2 isolates from the leaf part, Ba_2 from the stem part and Ri_2 from the rhizome part. The antibacterial activity of supernatant Ba_2 isolates showed the best effect compared to the supernatant of Da_2 and Ri_2 isolates. The diameter of the largest inhibition zone in the Ba_2 isolate against S. epidemidis of 26 mm which can be categorized very strongly where as in isolates of endophytic bacteria Ba_2 against P. aeruginosa of 13,99 mm which is categorized as strong.Keywords: Antibacteria, Dermatitis, Endophyte,Zingiber cassumunar